The The Development of An Android-Based Assessment Instrument To Assess Fifth-Grade Students' Cognitive Ability - Saraswati, Diah; Lestari, Wahyu; Haryani, Sri (Journal of Research and Educational Research Evaluation, 2021)
This study aims to develop an application product in the form of a valid, reliable, and practical cognitive assessment for Android. The research method is based on the ADDIE procedure, which consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Students in the fifth grade of an elementary school in Pemalang Regency served as research subjects. The following instruments were used in this study: observation sheets, questionnaire sheets, android-based applications, questionnaires for needs analysis and practicality, and documentation sheets. This research employs both quantitative and qualitative data analysis techniques. The results indicated that (1) expert evaluation of the product (expert judgment) suggested that the instrument was feasible to test on a small scale with revisions. (2) The ten instruments are empirically reliable in small- and large-scale trials. (3) Exploratory Factor Analysis (EFA) was used to determine the instrument's construct validity; all ten instrument constructs were valid. (4) The developed product takes the form of a functional Android application. The application product, which takes the form of an android-based cognitive assessment, demonstrates that it is valid, reliable, and practical.